Respuesta :

Answer:

[tex]y=(x-3)^2-6[/tex]

Step-by-step explanation:

[tex]y=x^2-6x+3[/tex]

This is written in the standard form of a quadratic function:

[tex]y=ax^2+bx+c[/tex]

where:

  • ax² → quadratic term
  • bx → linear term
  • c → constant

You need to convert this to vertex form:

[tex]y=a(x-h)^2+k[/tex]

where:

  • (h,k) → vertex

To find the vertex form, you need to find the vertex. For this, use the equation for axis of symmetry, since this line passes through the vertex:

[tex]x=-\frac{b}{2a}[/tex]

Using your original equation, identify the a, b, and c terms:

[tex]a=1\\\\b=-6\\\\c=3[/tex]

Insert the known values into the equation:

[tex]x=-\frac{(-6)}{2(1)}[/tex]

Simplify. Two negatives make a positive:

[tex]x=\frac{6}{2} =3[/tex]

X is equal to 3 (3,y). Insert the value of x into the standard form equation and solve for y:

[tex]y=3^2-6(3)+3[/tex]

Simplify using PEMDAS:

[tex]y=9-18+3\\\\y=-9+3\\\\y=-6[/tex]

The value of y is -6 (3,-6). Insert these values into the vertex form:

[tex](3_{h},-6_{k})\\\\y=a(x-3)^2+(-6)[/tex]

Insert the value of a and simplify:

[tex]y=(x-3)^2-6[/tex]

:Done